FENOMENA QUASI BROKEN HOME DALAM KELUARGA PEKEBUN - Podi Sastra Pramana Putra (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
Abstract: The quasi broken home phenomenon in the families of planters can be seen that, this family resembles the Broken Home family, where the relationship between parents and children does not work well. However, the parents are still intact. In addition, parents often leave children. This is caused by several factors, namely parents are busy with work so they do not have time and time to guide their children. Sometimes quasi broken home is caused by parents leaving children without news. The impact of quasi broken home on children's behavior is: children often go home late at night, skip school, fight, deny parents to even get drunk.Keywords: Phenomenon, Quasi Broken Home, Farmers.